The immediate and long-term effects of prenatal opioid exposure - Yen, Elizabeth; Davis, Jonathan M. (Frontiers in Pediatrics, 2022)
The opioid epidemic has adversely affected neonates and children, yet the mechanisms by which it impacts this population are not well understood. Not only does prenatal opioid exposure result in short-term consequences shortly after birth, it also creates long-term sequelae that may predispose these children to physical, emotional, psychiatric, cognitive, and socioeconomic problems in the future. This article aims to provide a scoping overview of the long-term effects of antenatal opioid exposure on neonates and children, as well as quality improvement and research efforts to understand and mitigate this major public health concern.